The human will in Judaism : the Mishnah's philosophy of intention - Eilberg-Schwartz, Howard, 1956- (Brown Judaic studies, 2020)
"In The Human Will in Judaism: The Mishnah's Philosophy of Intention, Howard Eilberg-Schwartz examines how the Mishnah, an early rabbinic document redacted around 200 CE, imagines the role of human intention in the fulfillment of God's laws."--